2023
DOI: 10.3389/fimmu.2023.1281056
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to pesticides dysregulates systemic Th1/Th2/Th17 cytokines and correlates with poor clinical outcomes in breast cancer patients

Stephany Bonin Godinho dos Santos,
Janaína Carla da Silva,
Hellen dos Santos Jaques
et al.

Abstract: Pesticides are compounds known to cause immunetoxicity in exposed individuals, which have a potential to substantially modify the prognosis of pathologies dependent on an efficient immune response, such as breast cancer. In this context, we examined the circulating cytokine profile of Th1/Th2/Th17 patterns in women occupationally exposed to pesticides and their correlation with worse prognostic outcomes. Peripheral blood samples were collected from 187 rural working women with breast cancer, occupationally exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Due to its uncertain characteristics, intermediate risk may imply the recurrence of disease or even systemic damage and has been linked to poor immunological pro les. Other studies have reported immune deregulation in women exposed to pesticides, 38,39 which may favor the development of more aggressive tumors. For example, failure to produce Th1 immune responses can in uence the development of large tumor masses in the long term, potentially resulting in aggressive tumor behaviors, such as the occurrence of metastases observed in the exposed patients described in this study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to its uncertain characteristics, intermediate risk may imply the recurrence of disease or even systemic damage and has been linked to poor immunological pro les. Other studies have reported immune deregulation in women exposed to pesticides, 38,39 which may favor the development of more aggressive tumors. For example, failure to produce Th1 immune responses can in uence the development of large tumor masses in the long term, potentially resulting in aggressive tumor behaviors, such as the occurrence of metastases observed in the exposed patients described in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Further aggravating harm to the health of the population exposed to pesticides, a study conducted on a population chronically exposed to pesticides-even at low exposure doses-found an accumulation of DNA lesions due to failures in the genetic material repair system. 42 Thus, the accumulation of mutations observed in the immune and in ammatory responses triggered by pesticide exposure, 3,31,38,39 which generally result in the inactivation of tumor suppressor genes, are indications of genomic instability. 43 This genomic instability increases susceptibility to metastasis development.…”
Section: Discussionmentioning
confidence: 99%